2013
DOI: 10.1039/c3nr01277h
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of anatase nanoparticles with fused ring salicylate-type ligands (3-hydroxy-2-naphthoic acids): a combined DFT and experimental study of optical properties

Abstract: The surface modification of nanocrystalline TiO2 particles (45 Å) with salicylate-type ligands consisting of an extended aromatic ring system, specifically 3-hydroxy-2-naphthoic acid, 3,5-dihydroxy-2-naphthoic acid and 3,7-dihydroxy-2-naphthoic acid, was found to alter the optical properties of nanoparticles in a similar way to salicylic acid. The formation of the inner-sphere charge-transfer (CT) complexes results in a red shift of the semiconductor absorption compared to unmodified nanocrystallites and a red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 87 publications
4
40
0
Order By: Relevance
“…2B). The determined molar ratio is in agreement with literature data concerning composition of CT complexes between surface Ti atoms and catecholate-or salicylate-type of ligands [26][27][28][29][30][31].…”
Section: Microstructural and Optical Properties Of Surface-modified Tsupporting
confidence: 91%
See 2 more Smart Citations
“…2B). The determined molar ratio is in agreement with literature data concerning composition of CT complexes between surface Ti atoms and catecholate-or salicylate-type of ligands [26][27][28][29][30][31].…”
Section: Microstructural and Optical Properties Of Surface-modified Tsupporting
confidence: 91%
“…By plotting 1/A versus 1/[L], the straight line was obtained, and from the ratio of the intercept and the slope, Kb value was found to be 3.76×10 3 M -1 . The determined stability constant is of the same order of magnitude as the reported values for surface-modified colloidal TiO2 NPs with catecholate-and salicylate-type of ligands[26][27][28][29][30][31].The stoichiometric ratio between Tisurf atoms and ligand (AA) in the CT complex was checked by Job's method of continuous variation[40] assuming that only one type of complex is present in solution. According to Job's method, the stoichiometric ratio (n) is determined from the plot of the absorbance as a function of the mole fraction (x) of metal or ligand.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…Several papers have investigated CT complex formation between catecholate [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] and salicylate [27,[36][37][38]40,41] type ligands and colloidal TiO 2 nanoparticles (d $ 45 Å), where the binding of modifiers induces the surface reconstruction of the nanoparticles. Recently, combined theoretical (DFT) and experimental studies were performed, mainly on catecholate-type molecules as surface modifiers of rutile [32] and anatase [33][34][35] TiO 2 nanoparticles, reporting different adsorption geometries.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, combined theoretical (DFT) and experimental studies were performed, mainly on catecholate-type molecules as surface modifiers of rutile [32] and anatase [33][34][35] TiO 2 nanoparticles, reporting different adsorption geometries. However, only a few papers have investigated the binding of salicylic acid [36][37][38]41]. Interfacial charge-transfer emission measurements and fluorescence anisotropy measurements [36] in catecholate-type molecule-TiO 2 nanoparticle complexes showed that the excitation is localized, with the charge transferred from the ligand to the localized Ti atom and not to the entire nanoparticle.…”
Section: Introductionmentioning
confidence: 99%